Toward instrument-free digital measurements: a three-dimensional microfluidic device fabricated in a single sheet of paper by double-sided printing and lamination1. Issue 4 (21st February 2015) - Jeong, Seong-Geun; Lee, Sang-Ho; Choi, Chang-Hyung; Kim, Jiyun; Lee, Chang-Soo
<x xml:space="preserve">Abstract</x> This study demonstrates a simple approach for fabricating a 3D-μPAD from a single sheet of paper by double-sided printing and lamination.